2004
DOI: 10.1016/j.jcat.2004.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt supported on zirconia and sulfated zirconia I. FT-IR spectroscopic characterization of the NOx species formed upon NO adsorption and NO/O2 coadsorption

Abstract: Cobalt catalysts are prepared by impregnating zirconia and sulfated zirconia using an aqueous solution of cobalt(II) acetate. XRD results show that the catalysts with 5 wt% cobalt loading contain a small amount of Co 3 O 4 . Analysis of the FT-IR results on the adsorption of NO at room temperature reveals the formation of cobalt(II) mono-and dinitrosyls. It is shown that the nitrosyls formed on the sulfate-free catalyst with 5 wt% cobalt loading are unstable on prolonged contact with NO at room temperature due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 38 publications
7
60
0
2
Order By: Relevance
“…It has been reported that the bands between 1200 and 870 cm −1 are attributed to the stretching vibrations of S-O. 48 Therefore, based on the FT-IR, it can be confirmed that SZ exists in the MIL-101s which is in agreement with the results of the elemental analysis for sulfur content and acid site density. The SEM images (Figure 6) of the SZ/MIL101s show that the morphologies of the SZ/MIL-101s are homogeneous even with the composing of MIL-101 with SZ.…”
Section: Resultssupporting
confidence: 82%
“…It has been reported that the bands between 1200 and 870 cm −1 are attributed to the stretching vibrations of S-O. 48 Therefore, based on the FT-IR, it can be confirmed that SZ exists in the MIL-101s which is in agreement with the results of the elemental analysis for sulfur content and acid site density. The SEM images (Figure 6) of the SZ/MIL101s show that the morphologies of the SZ/MIL-101s are homogeneous even with the composing of MIL-101 with SZ.…”
Section: Resultssupporting
confidence: 82%
“…4a. The spectral region between 1700 and 1200 cm −1 is characteristic for the nitrate and nitrite species coordinated on TiO 2 and ZrO 2 [28][29][30]. The observed frequencies at 1644 and 1209 cm −1 can be attributed to bridging nitrates, while the features at 1578, 1550 and 1280 cm −1 can be assigned to bidentate nitrates [8,31].…”
Section: Structural Characterization Of the Synthesized Materialsmentioning
confidence: 93%
“…Many elements supported on SZ have been shown to be active for the CH 4 -SCR reaction, including Ga [5], Pd [6][7][8][9], Rh [10], Co [11], Mn [12], and In [13]. Current research efforts have focused on the mechanism of the reactions over these catalyst [14][15][16] and on the improvement of the reaction activity of these catalyst by co-loading these element onto the SZr support, such as PdCo/SZr [17,18]. 2000, Chin et al reported on the high activity of a Pd/WZr catalyst and its high resistance to H 2 O and SO 2 for the reaction [19,20].…”
Section: Introductionmentioning
confidence: 99%